Social Networks and Perceptions of Intergroup Conflict: The Role of Negative Relationships and Third Parties - Labianca, Giuseppe; Brass, Daniel J.; Gray, Barbara (Academy of Management Journal, 1998)
This study investigated the relationship between interpersonal relationships among members of different departments and individuals' perceptions of intergroup conflict within an organization. Although friendships across groups were not significantly related to perceptions of intergroup conflict, negative relationships were associated with higher perceived intergroup conflict. Perceptions of intergroup conflict were also significantly related to indirect relationships through friends, and an amplification effect was uncovered. Finally, low intragroup cohesiveness was significantly related to higher perceptions of intergroup conflict.